GEOLOGICAL AND MINING CONDITIONS FOR THE EFFECTIVE DEVELOPMENT OF CONSTRUCTION AND CRUSHED STONE DEPOSITS WITHIN THE DISTRIBUTION OF GLACIAL SEDIMENTS - LUKOMSKYI, Vladyslav; KURYLO, Mariia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The study determined the feasibility of multucommodity deposits development of construction and crushed stone, which are localized within the distribution of glacial and fluvioglacial deposits. Overburden is studied as associated minerals, used in the construction industry and landscape design. The objects of the study are deposits of granites and labradorite, which have industrial reserves and are mined, as overburden rocks have enough thickness of fluvioglacial sediments. During the development of crystalline rock, fluvioglacial deposits in many cases are classified as overburden. Traditional mining methods of gravel-sand rocks are usually unsuitable or complicate the development, since the problem of extracting overburden fluvioglacial deposits, as a rule, does not exist at the stage of opening, but already in the mining process. The mining-geological features of fluvioglacial and glacial deposits make it necessary to adjust design solutions when developing crushed stone deposits to ensure the stability of the sides of the quarry and industrial safety requirements. There are the results of studying the geological structure of deposits of building stone and crushed stone within the boundaries of glacial deposits. These are the Sosnivske, Yaroshivske, Koshchiivske, Boguslavske deposits, the "Deshki" area, and the Ostriv deposit, as well as in the "Synii Kamin" block raw material deposit, where overburden rocks are presented by thick glacial and fluvioglacial layers of the flgPIIdn Dnieper climatolite. The following features of the geological structure within these deposits were fixed: 1) a significant change of the physical and mechanical properties of the rocks that make up the fluvioglacial deposits and their granulometric composition; 2) a variety of mining conditions, including the presence of layers of sandy-clay rocks; 3) different degrees of waterlogging of fluvioglacial deposits; 4) a significant change in quality indicators within one deposit. The timeliness and quality of the detection of these features affects the effectiveness of the development of fluvioglacial rocks as co-occurring or by-product mineral. For such reserves, it is recommended to develop and use cut-off parameters for mineral raw materials, which take into account specific mining and geological conditions, during geological and economic assessment.